Intracellular chromobody delivery by mesoporous silica nanoparticles for antigen targeting and visualization in real time - Chiu, Hsin-Yi (Sci Rep, 2016)
Chromobodies have recently drawn great attention as bioimaging nanotools. They offer high antigen binding specificity and affinity comparable to conventional antibodies, but much smaller size and higher stability. Chromobodies can be used in live cell imaging for specific spatio-temporal visualization of cellular processes. To date, functional application of chromobodies requires lengthy genetic manipulation of the target cell. Here, we develop multifunctional large-pore mesoporous silica nanoparticles (MSNs) as nanocarriers to directly transport chromobodies into living cells for antigen-visualization in real time. The multifunctional large-pore MSNs feature high loading capacity for chromobodies, and are efficiently taken up by cells. By functionalizing the internal MSN surface with nitrilotriacetic acid-metal ion complexes, we can control the release of His(6)-tagged chromobodies from MSNs in acidified endosomes and observe successful chromobody-antigen binding in the cytosol. Hence, by combining the two nanotools, chromobodies and MSNs, we establish a new powerful approach for chromobody applications in living cells.